2022
DOI: 10.1177/20406223221112561
|View full text |Cite
|
Sign up to set email alerts
|

Increased IL-31 expression in serum and tissue protein in prurigo nodularis

Abstract: Background: Prurigo nodularis (PN) is a chronic pruritic skin disease which can greatly impact patients’ quality of life. Moreover, the pathogenesis remains unclear, making it a difficult-to-treat condition. Aims: To investigate the expression of interleukin-31 (IL-31) in serum and skin biopsy specimens of PN patients and healthy subjects and identify its possible correlation to disease severity and itch intensity. Methods: Patients with PN and healthy volunteers were recruited for the study. Expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…In comparing cytokine levels of patients with PN to healthy controls, we found that IL-6, TNF-α, IL-12/IL23p40, MIP-1α/CCL3, MDC/CCL22, TSLP, IL-10, IL-15, sVCAM-1, sICAM-1, and SAA were significantly elevated. Prior studies have found elevated levels of CUB domain-containing protein 1 (CDCP1), Monocyte Chemotactic Protein 3 (MCP-3), IL-13, periostin, IL-31, IL-6, caspase 8, β-endorphin, and autotaxin in the blood of PN patients 5 7 , 23 25 . Several Th1/Th17 associated cytokines that were elevated in PN compared to HCs and have not been previously linked to PN include MIP-1α/CCL3 and IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…In comparing cytokine levels of patients with PN to healthy controls, we found that IL-6, TNF-α, IL-12/IL23p40, MIP-1α/CCL3, MDC/CCL22, TSLP, IL-10, IL-15, sVCAM-1, sICAM-1, and SAA were significantly elevated. Prior studies have found elevated levels of CUB domain-containing protein 1 (CDCP1), Monocyte Chemotactic Protein 3 (MCP-3), IL-13, periostin, IL-31, IL-6, caspase 8, β-endorphin, and autotaxin in the blood of PN patients 5 7 , 23 25 . Several Th1/Th17 associated cytokines that were elevated in PN compared to HCs and have not been previously linked to PN include MIP-1α/CCL3 and IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐31, a member of the IL‐6 cytokine family, is a pruritic proinflammatory cytokine 60 . Not surprisingly, IL‐31 levels are elevated in pruritic diseases such as atopic dermatitis, 19 prurigo nodularis, 61 lichen planus, 62 and uremic pruritus 63 . Furthermore, elevated IL‐31 levels have been reported in autoimmune diseases such as psoriasis, 64 systemic lupus erythematosus, 65 dermatomyositis, 66 bullous pemphigoid, 67 and subtypes of pemphigus including the non‐pruritic subtype pemphigus vegetans 68 …”
Section: Discussionmentioning
confidence: 99%
“…22 Erhöhte Konzentration von Interleukinen, wie IL-13 und IL-31, wurden im Blut von Patienten mit CNPG gefunden. [23][24][25][26] Bei CNPG wurde eine verringerte intraepidermale Nervenfaserdichte nachgewiesen, und die veränderte Neuroanatomie steht in Zusammenhang mit einer veränderten Nervenfaserfunktion und neuronaler Überempfindlichkeit. 15,18,27 Genetische Studien haben spezifische Varianten identifiziert, die mit CNPG assoziiert sind, unter anderem in der Nähe der Gene PLCB4 (Phospholipase C-β4) und TXNRD1 (Thioredoxin-Reduktase 1).…”
Section: Pathophysiologieunclassified